New inventory of glaciers in southeastern part of the Eastern Sayan Mountains - E. Yu. Osipov; A. Yu. Ashmetiev; O. P. Osipova; E. V. Klevtsov (Лëд и снег, 2015)
Satellite images with high (Quick Bird, 2006, WorldView-1, 2008, 0.5–0.6 m) and middle (Landsat-7 ETM +, 2001, 15–30 m) resolution were used to map contemporary glaciers on two mountain peaks of south-eastern part of East Sayan Ridge – Munky Sardyk (3491 m a.s.l.) and Topographov (3089 m a.s.l.). Topographic maps of 1978 and 1981 and Landsat-7 images (summer 2001) were used to assess glacier changes during second half of XX century. Modern terminal and lateral moraines near glacier snouts were used to reconstruct former outlines during the end of the Little Ice Age (middle of XIX century). Also SRTM data and GPS-surveys in Munku-Sardyk area were applied to measure glacier altitudes. GIS technologies allowed forming digital glacier data base with attribute information and new inventory was made. Totally 13 glaciers with area of 5.1 km² were investigated and mapped. Glaciers are located in vertical range from 2800–3490 m a.s.l. (Munku-Sardyk area) and 2340–2950 m a.s.l. (Topographov area). Firn line on glaciers vary from 2540 to 3110 m a.s.l., rising to the southeast. On average, over the past 160 years (since the end of the Little Ice Age) glaciers have significantly decreased. Ice area has decreased by 49%, length has diminished by 570 m, the glacier snouts has risen by 124 m. Analysis of regional climate data shows that the rate of deglaciation is well correlated with summer temperatures increasing in the second half of XX century, especially in 1980–1990s. A tendency to recover glacier mass balance was revealed during the last decade based on climatic data.